2012
DOI: 10.4236/ojgas.2012.24039
|View full text |Cite
|
Sign up to set email alerts
|

Appropriateness of colonoscopy in Cocody teaching hospital center in 2010: A prospective study using criteria established by the European panel on the appropriateness of gastrointestinal endoscopy (EPAGE)

Abstract: Aims: 1) To assess the feasibility of EPAGE criteria in clinical practice; 2) To assess appropriateness colonoscopy using EPAGE criteria; 3) To compare colonoscopy appropriateness and endoscopic lesions. Method: Hundred thirty-nine consecutive patients explored by colonoscopy were included. The appropriateness of colonoscopy was evaluated by EPAGE criteria. Results: EPAGE criteria were applicable among 127 patients (91% of the cases). Colonoscopies were appropriate, uncertain and inappropriate in respectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…Studies from all over the world have reported percentages within the range of for appropriateness of colonoscopy. Highest reported thus far according to EPAGE II evaluation is 80.4% [ 14 ], while the lowest (26%) is recorded from a multi-country study which involved 21 endoscopy centers from 11 countries [ 15 ]. One study from Ivory Coast, Africa found out an appropriateness percentage to be 40% [ 16 ], which is below our finding.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from all over the world have reported percentages within the range of for appropriateness of colonoscopy. Highest reported thus far according to EPAGE II evaluation is 80.4% [ 14 ], while the lowest (26%) is recorded from a multi-country study which involved 21 endoscopy centers from 11 countries [ 15 ]. One study from Ivory Coast, Africa found out an appropriateness percentage to be 40% [ 16 ], which is below our finding.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, many African countries are experiencing urbanization with adoption of Western diet associated with low residue. There is increasing availability of modern diagnostic investigations tools (e.g., colonoscopy) for accurate detection rate of colorectal diseases [7‒35]. Since there are common risk factors shared by colonic diverticulosis and colorectal neoplasia, there may also be a similar epidemiological trend of rising prevalence of diverticular disease as noted for colorectal cancer in some countries in Africa [9, 18, 19, 36‒38].…”
Section: Introductionmentioning
confidence: 99%
“…La maladie hémorroïdaire est une affection très fréquente des veines anales matérialisée par une dilatation des veines autour de l'anus ou du rectum et constitue de nos jours une cause plus fréquente de plaintes anales de consultation en Médecine générale. [1][2][3][4] , avec une prévalence qui varie entre 4,4% et 86% [4][5][6][7] .Il existe une thérapeutique bien définie. Cependant dans notre pays, il a été constaté depuis belle lurette, que le traitement des crises hémorroïdaires a été du ressort de la médecine traditionnelle [8].…”
Section: Introductionunclassified